2022
DOI: 10.1002/hsr2.560
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Nutritional Risk Index assessment in elderly patients during the COVID‐19 outbreak

Abstract: Background and Aims: Globally, coronavirus disease-2019 (COVID-19) is persistent in many countries and presents a major threat to public health. Critically, elderly individuals, especially those with underlying disease, poor nutritional and immune functions, are highly susceptible. Therefore, we analyzed the epidemiological features in elderly COVID-19 patients.Methods: In total, 126 patients were recruited in the Fifth Affiliated Hospital of Sun Yat-sen University, China from January 2020 to March 2020 (inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…GNRI is the geriatric nutritional risk index, 22 which integrates three indicators of serum albumin level, actual weight and ideal weight, and GNRI score is proportional to the nutritional status of the patient, and can more fully reflect the nutritional status of the patient’s body. 51 , 52 Related studies have shown 53 that GNRI assessment may provide valuable information for predicting the prognosis of COVID-19 pneumonia in older adults. Several previous studies have attempted to compare the GNRI with other standardized indices such as the MNA and the GNRI, and have found the GNRI to be valid for use in older adults, but mostly in combination with other indices.…”
Section: Discussionmentioning
confidence: 99%
“…GNRI is the geriatric nutritional risk index, 22 which integrates three indicators of serum albumin level, actual weight and ideal weight, and GNRI score is proportional to the nutritional status of the patient, and can more fully reflect the nutritional status of the patient’s body. 51 , 52 Related studies have shown 53 that GNRI assessment may provide valuable information for predicting the prognosis of COVID-19 pneumonia in older adults. Several previous studies have attempted to compare the GNRI with other standardized indices such as the MNA and the GNRI, and have found the GNRI to be valid for use in older adults, but mostly in combination with other indices.…”
Section: Discussionmentioning
confidence: 99%
“…Pengetahuan dan sikap masyarakat terhadap infeksi akan mempengaruhi ketaatan dan kemandirian dalam perilaku untuk menghindari infeksi (Abualhommos et al, 2021). Pengetahuan ini juga akan mendukung program pencegahan infeksi lain seperti imunisasi (Moeed et al, 2022) dan upaya pemenuhan gizi yang baik untuk ketahanan tubuh (Yuan et al, 2022).…”
Section: A Latar Belakangunclassified